Hibah in the light of justice in Islam: jurists perspective - Awang, Abdul Bari (s.n, 2012)
This study explores selected issues related to the bestowal of gifts (hibah) by parents to their children. Hibah is a recognized way of surrendering property or wealth in Islam which is otherwise distributed according to fixed proportions (fara’id). Hibah goes back to the example of Prophet Muhammad (p.b.u.h) but it a potentially problematic practice because a gift rendered to one child with the exclusion of other siblings may be interpreted as preferential and therefore unjust treatment. The question arises thus of how justice can be preserved in giving away property and money in hibah. Furthermore, to which extent is it permissible to distribute property and wealth unequally among one’s children? Certain special conditions which bear upon the permissibility of hibah are discussed in reference to established views of classical as well as contemporary Muslim jurists. The writer concludes with his own conclusions and personal recommendations at the end of study.